1993
DOI: 10.1046/j.1537-2995.1993.33393174445.x
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion‐associated transmission of human T‐lymphotropic virus types I and II: experience of a regional blood center

Abstract: During a 22-month period, 78,000 blood donors were screened for human T-lymphotropic virus types I and II (HTLV-I/II) at Belle Bonfils Memorial Blood Center (Denver, Colorado). Positive donors and the living recipients of their previously donated blood components were evaluated for risk factors and symptoms related to HTLV-I infection, were screened by enzyme immunoassay, confirmed by Western blot for HTLV-I/II, and subsequently tested by polymerase chain reaction and peptide enzyme immunoassay to distinguish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In the US and other nonendemic regions, HTLV‐I has been spread by travelers and emigrants from HTLV‐I‐endemic areas, particularly by sexual transmission to women 3,4 . In our study, all six HTLV‐I‐infected persons were men, and follow‐up interviews identified a risk factor for five.…”
mentioning
confidence: 56%
“…In the US and other nonendemic regions, HTLV‐I has been spread by travelers and emigrants from HTLV‐I‐endemic areas, particularly by sexual transmission to women 3,4 . In our study, all six HTLV‐I‐infected persons were men, and follow‐up interviews identified a risk factor for five.…”
mentioning
confidence: 56%
“…Human T-lymphotropic virus is involved in adult T cell leukaemia and spastic paraparesis. This virus can be transmitted through blood [79][80][81][82] and, in a dental setting, it can infect via sharp instruments injuries [10].…”
mentioning
confidence: 99%